Petro physical properties analysis of beani bazar gas field, Bangladesh using wireline log interpretation - Islam, G. M. Ariful; Nipa, Farzana Yeasmin; Shah, Md. Shaheen (International Journal of Advanced Geosciences, 2017)
The study on analysis of petro physical properties which are done into two well such as BB-1 and BB-2 of Beani Bazar Gas Field using wire line log data. In BB-1, Upper Gas Sand (UGS), Lower Gas Sand (LGS), Sand-1 and Bellow Lower Gas Sand (BLGS) zones and in BB-2, UGS and LGS are identified through high gamma ray log, high resistivity, low neutron and low density log response. The thickness of UGS, LGS, Sand-1, BLGS of BB-1 and UGS, LGS of BB-2 are respectively 47.69m, 14.326m, 17.526m, 17.526m and 26.37m, 21.03m. The Shale volumes of UGS, LGS, Sand-1 and BLGS of BB-1 are respectively 14.87%, 21.58%, 11.69% and 21.28% and UGS and LGS of BB-2 are respectively 17.91% and 29.33%, which are measured through Schlumberger Clavier method. The average porosity of UGS, LGS, Sand-1 and BLGS of BB-1 are respectively 17.55%, 16.60%, 18.07% and 31.10% and UGS and LGS of BB-2 are respectively 13.19% and 11.29%, which are very effective for hydrocarbon prospect by using neutron-density combination method. The average water saturations of UGS, LGS, Sand-1 and BLGS of BB-1 are respectively 24.97%, 23.78%, 80.18% and 19.85% which revised to hydrocarbon saturations as respectively 75.03%, 76.22%, 19.82% and 80.15% and UGS and LGS of BB-2 are respectively 41.20% and 69.50% which revised to hydrocarbon saturations as respectively 58.80% and 30.50% that are followed by Simandoux method. By analysis of petro physical properties of those zones, the UGS and LGS are very effective hydrocarbon bearing zones where production is running at the present time, the Sand-1 zone is water bearing zone. This study impose high important on BLGS. This zone is satisfied all criteria for hydrocarbon prospect. This study recommends that more study is needed for BLGS, and it may be commercially economical viable in a future.